The New York Times on the Supreme Court, 1857-2008 - Jost, Kenneth (TimesReference from CQ Press)
'The New York Times on the Supreme Court' uses articles from 'The New York Times' to explore the history and influence of the Supreme Court. Author Kenneth Jost provides analysis and presents selected news stories, letters to the editor, and Op Ed essays from the paper to look at the development of the Court and its relationship to the other branches of government and to the states. Later chapters explore key themes - including freedom of ideas, the rights of political participation, equal protection of the law, crime and punishment - and the appropriate major cases, which are accompanied by decision dates, verdicts, and who wrote the majority opinion